Effectiveness of germinated brown rice on metabolic syndrome: A randomized control trial in Vietnam - Truong Tuyet Mai; Tran Thu Trang; Tran Thi Hai (AIMS Press, 2020)
To treating Metabolic Syndrome (MetS) in the human body by using cooked pre- germinated brown rice (PGBR), a randomized control trial was done in Vietnam. 80 subjects (65.1 ± 3.81 years old) separated into two groups in pairs were assigned a daily intake of 200 g PGBR, and the subjects in the placebo group were kept in normal living ways (consuming white rice). Before baseline and after 3 months of the intervention, anthropometric measurements, blood chemical examinations, a nutrition survey, and physical activity measurements were conducted. The main finding showed that the percentages of patients with MetS in the PGBR group were reduced significantly compared to the placebo group (p < 0.05). Serum HDL cholesterol concentrations were significantly increased from 1.11 (mmol/l) to 1.44 (mmol/l) compared to the placebo group (p < 0.05). The findings suggest that PGBR may affect HDL cholesterol, PGBR might be considered in reducing the risk of MetS in Vietnam.